A language-in-use study of EFL students’ social discourses in project-based learning - Bello Vargas, Ingrid (Colombian Applied Linguistics Journal, 2012)
This article is based on a qualitative research study that was conducted to explore students’ discourses as citizens in an English as a Foreign Language (EFL) course. A pedagogical intervention was proposed in order to bridge the existing gap. The instructional design consisted of PBL sessions with a coeducational group of eighteen undergraduate students, who worked collaboratively to discuss social issues while studying the target language (TL). Student artifacts, transcriptions of project oral reports, and a conference with the participants were used to gather the data. Following a discourse analysis approach, three main discourses were identified to show the learners’ social representations, their critical stand on topical issues, and their interest in social transformations. Overall, the findings suggest that the students’ views of social reality are diverse, contradictory, and changing, and that the EFL class can become a site for citizenship education when the TL is presented as a tool to facilitate self-expression and critical reflection.